Exotic animal hematology and cytology - Campbell, Terry W., 1949- (Ames, Iowa : John Wiley & Sons Inc., 2015)
Exotic Animal Hematology and Cytology, Fourth Edition updates the most comprehensive reference available on exotic animal hematology and cytology of all major species. Acts as both an atlas and a text, offering high-quality photographs and step-by-step descriptions of techniques associated with preparing and interpreting hematology and cytology samplesPresents complete information on hematology and cytology in a wide range of exotic species, including small mammals, birds, reptiles, amphibians, and fishIncludes more than 700 high-quality color photographs, now with sizing barsTakes a new dis.
Peripheral blood of mammals -- Peripheral blood of birds -- Peripheral blood of reptiles -- Peripheral blood of amphibians -- Peripheral blood of fish -- Blood parasites -- Bone marrow/hematopoiesis -- Blood sample collection and preparation in small mammals -- Blood sample collection and preparation in birds -- Blood sample collection and preparation in reptiles -- Blood sample collection and preparation in amphibians -- Blood sample collection and preparation in fish -- Bone marrow collection and evaluation -- Normal mammalian cytology -- Normal avian cytology -- Normal herptile cytology -- The cytology of inflammation -- Hyperplasia and benign neoplasia -- Malignant neoplasia -- Effusions -- Infectious agents -- Cytology sampling and evaluation -- Wet mount microscopy in fish -- Wet mount preparations for evaluation of fish.
Preceded by Avian and exotic animal hematology and cytology / Terry W. Campbell and Christine K. Ellis. 3rd ed. 1995.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Exotic animals -- Diseases; Exotic animals -- Diseases -- Treatment; Veterinary hematology; Veterinary cytology; Exotic animals -- Diseases -- Treatment; Exotic animals -- Diseases; Veterinary cytology -- Case studies; Veterinary cytology; Veterinary hematology -- Case studies; Veterinary hematology; Animal Diseases -- diagnosis; Animals, Domestic -- physiology; Cytodiagnosis -- veterinary; Hematologic Tests -- veterinary; Pets -- physiology; Electronic books; Electronic books